2020
DOI: 10.5194/amt-13-5335-2020
|View full text |Cite
|
Sign up to set email alerts
|

Application of the shipborne remote sensing supersite OCEANET for profiling of Arctic aerosols and clouds during <i>Polarstern</i> cruise PS106

Abstract: Abstract. From 25 May to 21 July 2017, the research vessel Polarstern performed the cruise PS106 to the high Arctic in the region north and northeast of Svalbard. The mobile remote-sensing platform OCEANET was deployed aboard Polarstern. Within a single container, OCEANET houses state-of-the-art remote-sensing equipment, including a multiwavelength Raman polarization lidar PollyXT and a 14-channel microwave radiometer HATPRO (Humidity And Temperature PROfiler). For the cruise PS106, the measurements were suppl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 96 publications
(120 reference statements)
1
37
0
Order By: Relevance
“…PAS-CAL as well as ACLOUD was dedicated to the investigation of processes related to Arctic amplification. During the full period of PS106, continuous remote sensing of aerosols and clouds was performed with the OCEANET-Atmosphere platform aboard Polarstern (Griesche et al, 2020b). The suite of instruments of OCEANET operated during PS106 is listed in Table 1.…”
Section: Instrumentation and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…PAS-CAL as well as ACLOUD was dedicated to the investigation of processes related to Arctic amplification. During the full period of PS106, continuous remote sensing of aerosols and clouds was performed with the OCEANET-Atmosphere platform aboard Polarstern (Griesche et al, 2020b). The suite of instruments of OCEANET operated during PS106 is listed in Table 1.…”
Section: Instrumentation and Methodologymentioning
confidence: 99%
“…In turn, ground-based profiling studies from the Arctic, which rely on lidar and radar observations, usually provide reasonable data only at heights above 100-150 m above ground, as is the case for the 35 GHz cloud radar (KAZR) of the US Department of Energy (DOE) Atmospheric Radiation Measurement (ARM) program at the NSA (North Slope of Alaska) site in Utqiaġvik (formerly known as Barrow), USA. Cloud processes that take place at lower heights can thus not thoroughly be characterized (Griesche et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In a laboratory study, Hallett and Mossop (1974) observed that rimesplintering is active at temperatures between −3 and −8 • C when particles grow by riming. Dong and Hallett (1989) showed that at temperatures above −3 • C, droplets spread out on the ice surface and do not build an ice shell, while at temperatures below −8 • C the ice shell of rime might be too strong to break (Griggs and Choularton, 1983). While several observations of secondary ice could be explained by the rime-splintering process (e.g., Ono, 1971Ono, , 1972Harris-Hobbs and Cooper, 1987;Bower et al, 1996), secondary ice was also observed in cases where these requirements were not fulfilled (e.g., , or the SIP by rimesplintering alone was expected to be too slow to explain the observed rapid glaciation (e.g., Hobbs and Rangno, 1990).…”
Section: Secondary-ice Production Mechanismsmentioning
confidence: 99%
“…The coefficients are defined as positive, which means that the flux is directed against the mean gradient. Values of K can be derived from parameterizations based on turbulence observations such as proposed by Hanna (1968) or by directly applying Eq. (6) with the measured H , yielding K H .…”
Section: Vertical Profiles Of Turbulent Moisture and Heat Fluxesmentioning
confidence: 99%